2009
DOI: 10.1007/s10592-009-9839-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellite markers for Brachiaria brizantha (Hochst. ex A. Rich.) Stap

Abstract: The first set of nuclear simple sequence repeat (SSR) loci for Brachiaria brizantha (Hochst. ex A. Rich.) Stap is described. A microsatellite-enriched library was constructed and 19 loci were characterized. About 13 SSR loci were found to be polymorphic and across-taxa amplification tests showed that six of them can be transferred to four other species of Brachiaria. This new SSR resource will be a powerful tool for population genetic studies of B. brizantha, for interspecific genetic studies within the genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
2
12
1
1
Order By: Relevance
“…In B. brizantha [15], 96 clones from an enriched library were sequenced, 19 primer pairs were designed and tested, and 13 of those were polymorphic. A new set of 15 polymorphic primers for this species was published by Vigna et al [16], using the same enriched library.…”
Section: Discussionmentioning
confidence: 99%
“…In B. brizantha [15], 96 clones from an enriched library were sequenced, 19 primer pairs were designed and tested, and 13 of those were polymorphic. A new set of 15 polymorphic primers for this species was published by Vigna et al [16], using the same enriched library.…”
Section: Discussionmentioning
confidence: 99%
“…The 15 new SSRs presented in this study, along with five previously reported loci (Jungmann et al 2009b), were used to characterize the genetic diversity of the 172 accessions and six commercial cultivars of B. brizantha preserved in the EBC germplasm collection ( Table 2). The degree of polymorphism found in these loci among 178 genotypes was highly correlated with the degree of PIC values obtained from 23 accessions.…”
Section: Microsatellite Characterization In B Brizanthamentioning
confidence: 99%
“…This type of marker was also used by Ambiel et al (2008) to analyze the same materials studied by Machado Neto et al (2002). The most recent study used microsatellites to evaluate 23 accessions of this species together with one genotype of each of the following Brachiaria species: B. ruziziensis, B. humidicola, B. decumbens and B. dictyoneura (Jungmann et al 2009a). Despite B. brizantha being studied together with other Brachiaria species in these four works, an evaluation of a definitive number of accessions has not been conducted until now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A genomic library was constructed using one B. humidicola genotype, following the methodology of Billotte et al (1999) and according to Jungmann et al (2009). A total of 384 clones were sequenced in an ABI 377 automated sequencer (PE Applied Biosystems) using the BigDye Terminator Cycle Sequencing Kit (Applied Biosystems).…”
mentioning
confidence: 99%